Cotton crop irrigation planning (Gossypium hirsutum L.) through an integral programming model at 075 District, Sinaloa, Mexico - Sifuentes Ibarra, Ernesto (2014)
Cotton crops were one of the most important during the 50 and 80 decades in Northern Sinaloa, Mexico from the economical point of view. However, external factors such as monoculture and sanitary issues caused its disappearance. Due to the need of diversifying the actual pattern of crops grown in the zone, a great possibility of re-growing cotton crop exists. Actually, there is lack of updated information about irrigation and agronomic management practices of the crop. In order to contribute to a new crop planning, an integral programming model was used to estimate planting dates and windows as well as irrigation planning at different operation levels. Field experiments were conducted at different locations of northern Sinaloa during the growing season 2011-2012 in Ahome and Guasave counties. Each plot had a dimension of 2 hectares and five varieties grown with the purpose of calibrating the integral model to then realize a set of simulations with seven planting dates, estimate water requirements and length of growing season as well. At the end of the season (harvest) 2400 growing degree days were accumulated (100% open balls) for local conditions, water requirements were 500 mm for the month of July, 870 mm for October, after that it declined to a point of 690 mm for crops planted in January.